Thermally stable Sm3+ doped SrCeO3 single-phase white phosphor with Y3+ sensitization for fabricating wLEDs - C. K. Shilpa; S. V. Jasira; V. P. Veena; S. V. Sajith; A. M. Huda Thasneem; K. Greeshma; S. S. Ancy; Sakthivel Pandurengan; K. M. Nissamudeen (Scientific Reports)
Abstract The pioneering study reveals the transformative power of co-doping in enhancing phosphor performance, focusing on the development of a cutting-edge white phosphor: SrCeO3:0.02Sm3+ co-doped with Y3+ (0–2 wt%) for high-CRI white LED applications. These innovative perovskites were synthesized using a low-temperature fuel-excess gel combustion technique, with citric acid as the fuel and ammonium nitrate as an additional oxidizer. By examining the impact of Y3+ sensitization on the crystalline phases, morphology, elemental composition, band gap energy, and luminescence properties, the study discovered that orthorhombic SrCeO₃:0.02Sm3+: Y3+ perovskites exhibit exceptional crystallinity and peak luminescence at 1.5 wt% Y3+. The CIE color diagram confirmed their bright white light emission across all samples. This breakthrough positions nano-perovskite SrCe0.965Sm0.02O3:1.5 wt% Y3+ as a top candidate for direct phosphor coatings on near-UV LED chips, and its practical utility promises significant advancements in energy-efficient lighting technology.